BVGer D-3349/2021 vom 9. Juli 2021 - Bundesverwaltungsgericht (2021)
Asyl und Wegweisung (Mehrfachgesuch/Wiedererwägung) | Asyl und Wegweisung (Mehrfachgesuch/Wiedererwägung); Verfügung des SEM vom 9. Juli 2021